Vitamin D treatment of peripheral blood mononuclear cells modulated immune activation and reduced susceptibility to HIV-1 infection of CD4+ T lymphocyte (2019)
ABSTRACT: Introduction: Mucosal immune activation, in the context of sexual transmission of HIV-1 infection, is crucial, as the increased presence of activated T cells enhance susceptibility to infection. In this regard, it has been proposed that immunomodulatory compounds capable of modulating immune activation, such as Vitamin D (VitD) may reduce HIV-1 transmission and might be used as a safe and cost-effective strategy for prevention. Considering this, we examined the in vitro effect of the treatment of peripheral blood mononuclear cells (PBMCs) with the active form of VitD, calcitriol, on cellular activation, function and susceptibility of CD4+ T cells to HIV-1 infection. Methods We treated PBMCs from healthy HIV unexposed individuals (Co-HC) and frequently exposed, HIV-1 seronegative individuals (HESNs) from Colombia and from healthy non-exposed individuals from Canada (Ca HC) with calcitriol and performed in vitro HIV-1 infection assays using X4- and R5-tropic HIV-1 strains respectively. In addition, we evaluated the activation and function of T cells and the expression of viral coreceptors, and select antiviral genes following calcitriol treatment. Results Calcitriol reduced the frequency of infected CD4+ T cells and the number of viral particles per cell, for both, X4 and R5-tropic viruses tested in the Co-HC and the Ca-HC, respectively, but not in HESNs. Furthermore, in the Co HC, calcitriol reduced the frequency of polyclonally activated T cells expressing the activation markers HLA-DR and CD38, and those HLA-DR+CD38-, whereas increased the subpopulation HLA-DR-CD38+. Calcitriol treatment also decreased production of granzyme, IL-2 and MIP-1β by T cells and increased the transcriptional expression of the inhibitor of NF-kB and the antiviral genes cathelicidin (CAMP) and APOBEC3G in PBMCs from Co-HC. Conclusion Our in vitro findings suggest that VitD treatment could reduce HIV-1 transmission through a specific modulation of the activation levels and function of T cells, and the production of antiviral factors. In conclusion, VitD remains as an interesting potential strategy to prevent HIV-1 transmission that should be further explored.